Berlin Furniture Drawings by Carl Wilhelm Marckwort (1798-1875) - Stiegel, Achim (The Rijksmuseum Bulletin, 2020)
The Rijksmuseum recently acquired eight furniture designs, drawn by the cabinet-maker from Braunschweig, Carl Wilhelm Marckwort (1798-1875), while working as a journeyman in Berlin, in the years 1820-23. Apart from another group by Marckwort, no similar drawings made in Berlin during the first half of the nineteenth century survive, although they must once have been common. They were not regarded as works of art, and those that may have been retained in Berlin were lost during the Second World War. Marckwort took his drawings with him when he returned to Braunschweig in 1824, where they have until recently been kept by a succession of local cabinet-makers.Marckwort’s drawings present much information on current Berlin furniture types, and they document the high level of draughtsmanship attained by a talented craftsman working there. In Berlin, as in Vienna and indeed also in Braunschweig, much attention was given from the late eighteenth century onwards to providing drawing lessons for apprentices and journeymen. This was seen as an important step in an effort to improve the quality of manufactured goods. Marckwort’s manner of drawing, linear rather than free, exemplifies the workings of the new educational system. Sadly, no documentation concerning his training has been found.